2009
DOI: 10.1002/jssc.200900270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydrophilic metabolites in physiological fluids by HPLC‐MS using a silica hydride‐based stationary phase

Abstract: Aqueous normal-phase chromatography was used for the analysis of metabolites in human saliva and urine samples. The column was packed with a silica hydride type separation material. Several gradients were tested with different mobile phase additives in order to produce retention for amino acids, small organic acids, and carbohydrates. Detection was done by TOF MS. In some cases the relative concentration levels of various metabolites in human saliva were compared for normal patients and patients with pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…Two of the columns investigated in this study were found to be useful for the studies of retention of nucleotides: a Cogent DH HPLC column, already used in the analysis of many metabolites and polar compounds [8,9], and a UDA weak cation exchange, carboxylic acid HPLC column. A hydride-based C-18 was also tested for the sake of completeness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the columns investigated in this study were found to be useful for the studies of retention of nucleotides: a Cogent DH HPLC column, already used in the analysis of many metabolites and polar compounds [8,9], and a UDA weak cation exchange, carboxylic acid HPLC column. A hydride-based C-18 was also tested for the sake of completeness.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ANP analysis of polar compounds is achieved at high concentration of the organic solvent in the mobile phase (usually acetonitrile, but acetone may be used as well), which provides increased sensitivity. When MS detection is used, the analysis can be performed without derivatization of any substrates, including highly polar amino acids, sugars and presumably sugar-phosphates, which are also present in biological samples [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, LC-MS can be divided into dozens of different methods that target different compound classes, from highly hydrophilic metabolites using novel aqueous normal phase columns (Silica-Hydride columns) (Pesek et al, 2009) or zwitterionic hydrophilic interaction columns (HILIC) (Strege, 1998) to various reverse phase columns that cover wide XlogP lipophilicity ranges. Secondly, LC effluents can be used in combination with more than one detector, for example using a diode array detector for carotenoid detection in conjunction with a mass spectrometer for ionizable compounds (Lu et al, 2007).…”
Section: Liquid Chromatography -Tandem Mass Spectrometrymentioning
confidence: 99%
“…Silica hydride based stationary phases have been employed for bioanalysis, although the term aqueous NPC (ANPC) was preferred [15][16][17]. The chiral separation of drug substances was achieved using a cyclodextrin-derivatised stationary phase [18].…”
Section: Introductionmentioning
confidence: 99%